Almost preenvelopes of commutative rings (2012)
We study almost F-preenvelopes in the category of rings, for a significative class F of commutative rings. We completely identify those rings which have an almost F-preenvelope when F is the class of fields,semisimple rings, integer domains and local rings. We show that rings with Krull dimension zero have (almost) V-preenvelopes, where V is the class of von Neumann regular rings.